Developing A Reflective Thinking Tendency Scale for Teachers and Student Teachers - Semerci, Cetin (Edam, 2007)
This paper aims to develop the Reflective Thinking Tendency Scale (RTTS) for teachers and student teachers. Survey was the research method used in the study. In this research, there were 599 cases and 456 of these cases were the students of the departments of the Turkish language teaching and primary school teaching within grades of 2nd, 3rd and 4(th) at Firat University. The total number of students who attended the classes mentioned above was 960. The ratio of the population to the sample was 47.5%. The rest of the cases were composed of 143 primary school teachers (6th, 7th, 8(th) grades) who worked in Cermik in the city of Diyarbakir. The total number of teachers who worked in Cermik was 194. In this else, the ratio of the population to the sample was 71%. According to the factor analysis results, KMO value of the RTTS was 0.91 and the value of Barlett test was 6811.46 (p < .05). In this scale, there are 7 factors: Continuous and intentional thinking, open-mindness, effective and interrogated teaching, responsibility of teaching and science, foresighted and sincere, researcher and looking professional, The results; of the RTTS show that total correlation of items changed between 0.31 and 0.61 and it was found that the test-retest correlation was 0.74 (p < .01) and split half correlation coefficient was 0.77 (P < .01). The correlation between the scale and the 51 item the California Critical Thinking Scale (Kokdemir, 2003, 80-82) was 0,69 and the correlation coefficient between Semerci (2000, 23-26)'s Critical Thinking Skills Scale was 0.61 (p < .01). Cronbach alpha coefficient of the RTTS was 0.91. The scale consisted of 20 negative and 15 positive items. These results indicate that the scale had validity and reliability. The scale can be used with teachers and student teachers.
Keywords: Reflective thinking; teacher; student teachers